Plecanatide for the treatment of chronic idiopathic constipation in adult patients. Issue 11 (2nd November 2019) - Bassotti, Gabrio; Usai Satta, Paolo; Bellini, Massimo
ABSTRACT: Introduction . Chronic idiopathic constipation (CIC) is a functional gastrointestinal disorder that is associated with an increased healthcare cost and an abnormally poor quality of life. Plecanatide is a natural analog to the peptide agonist of the guanylate cyclase-C (GC-C) receptor, uroguanylin. The conversion of guanosine 5-triphosphate to cyclic guanosine monophosphate results in an increased bowel fluid secretion. Plecanatide is a promising new agent for CIC unresponsive to current therapeutic regimes. Areas covered . A comprehensive online search of Medline and the Science Citation Index was made using the keywords 'plecanatide', 'guanylate cyclase-C agonists', and 'constipation', in various combinations. We reviewed the pharmacodynamics, pharmacokinetics, and metabolism of this agent, and the most significant studies regarding the clinical efficacy and safety of plecanatide in CIC therapy. Expert opinion . Experimental studies showed that plecanatide was significantly better than placebo in reducing CIC severity, straining, stool consistency, bowel movements and quality of life. Apart from limited cases of diarrhea, no serious adverse events were reported. However, few data are available on its long-term safety. Furthermore, patients' affordability of plecanatide can be limited by its costs. Finally, this new agent with a different way of action can be proposed in patients refractory to common therapy.